A Highly Efficient Method for the Synthesis of Novel 1′H-spiro[indene-2, 2′-quinazoline]-1, 3, 4′(3′H)-trione Derivatives. (September 2015) - Sadat-Ebrahimi, Seyed Esmail; Irannezhad, Soroor; Moghimi, Setareh; Yahya-Meymandi, Azadeh; Mahdavi, Mohammad; Shafiee, Abbas; Foroumadi, Alireza
A Series of Novel Ninhydrin-derived Spiro-quinazolinone Derivatives in Moderate to Good Yields Have Been Synthesised Through a Ferric Chloride Catalysed Reaction in 1, 2-dichloroethane.